Evaluation and Improvement of Marketing Strategy of Lexiderm at PT Biofarma - Putra, Ronaldo Bagus; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2013)
The decrease of sales in export sector, triggered with the development of private hospitals make PT. Biofarma starts focusing on private sector by cooperating with PT. Compose Element to distribute Hydrogel modern wound care dressing named Lexiderm. The obstacles such as poor socialization, lack of coordination between distributor and marketing division, lack of education and promotion make the marketing strategy becomes less effective and less efficient. However, VMI (Vendor Managed Inventory) and collaboration between the involved parties will facilitate the marketing strategy to become integrated and coordinated. The right promotion to achieve targeted goal needs to be formulated so that sales will increase and brand awareness will improve. Evaluation measures the sales target, service level and on time delivery service and possible to implement.Â Keywords: Marketing a new product, marketing strategies, supply chain collaboration